Immunogenicity and safety of 3-dose primary vaccination with combined DTPa-HBV-IPV/Hib vaccine in Canadian Aboriginal and non-Aboriginal infants. Issue 16 (15th April 2015) - Scheifele, David W.; Ferguson, Murdo; Predy, Gerald; Dawar, Meena; Assudani, Deepak; Kuriyakose, Sherine; Van Der Meeren, Olivier; Han, Htay-Htay
Highlights These are the first available data on immune responses of Canadian Aboriginal infants to routine vaccines. Responses of Aboriginal and non-Aboriginal infants were compared after 3 doses of a hexavalent combination vaccine. Responses to H. influenzae b and hepatitis B components were at least as high in Aboriginal as in non-Aboriginal infants.